Peran Tokoh Pangeran Kuning Dalam Perlawanan Terhadap Penjajahan Belanda Pada Perang Tebidah Tahun 1856-1857 - Yuristin, Puput Titania Elisa; Firmansyah, Andang; Firmansyah, Haris (Universitas Syiah Kuala, 2025)
This research aims to find out the history of Prince Kuning's struggle against the Dutch colonialists during the Tebidah War in 1856-1857. The method used is a historical research method consisting of topic selection, heuristics, verification, interpretation, historical writing. The research approach used by researchers is sociology, because it involves the royal family, social layers of society such as the Dayak and Malay tribes. Research results: Ade Hasan, whose title is Pangeran Kuning Suryapati or better known to the public as Prince Kuning, was a figure opposing Dutch colonialism in the 19th century. The spirit and courage of the Yellow Prince were embedded and burning. Together with the Dayak and Malay tribes in Nanga Kayan, Prince Kuning opposed Dutch colonialism which was marked by the Tebidah War which occurred in 1856-1857. The role and values that Prince Kuning instilled in fighting Dutch colonialism were deeply embedded in the Sintang people. Prince Kuning had shaken the position of the Dutch government which at that time ruled the land of the Sintang Kingdom. So with their nationalist attitude, the people of Sintang honored Prince Kuning with the erection of the Prince Kuning Statue Monument in the city of Sintang.